Sexual Harassment in the Information Age: The Human Resource Manager's Guide to Nontraditional Sexual Harassment - Angelina C. Toomey; Allen F. Wysocki (EDIS)
HR028, a 4-page fact sheet by Angelina C. Toomey and Allen F. Wysocki, helps human resource managers recognize types of nontraditional sexual harassment and gives strategies managers can take to ensure a workplace that is free from all types of harassment or prejudicial treatment. Includes references. Published by the UF Department of Food and Resource Economics, December 2009.